Peptide-based targeting of the platelet-derived growth factor receptor beta - Askoxylakis, Vasileios; Marr, Annabell; Altmann, Annette; Markert, Annette; Mier, Walter; Debus, Jürgen; Huber, Peter E.; Haberkorn, Uwe (Molecular imaging & biology, 2013)
PURPOSE: The aim of this work is to identify new ligands targeting the platelet-derived growth factor receptor beta (PDGFRβ). PROCEDURES: Biopanning was carried out with a 12-amino-acid phage display library against the recombinant extracellular domain of PDGFRβ. The identified peptide PDGFR-P1 was chemically synthesized and labeled with (125)I or (131)I. In vitro studies were performed on the PDGFRβ-expressing cell lines BxPC3 and MCF7 and on PDGFRβ-transfected HEK cells in comparison to negative control wtHEK293 and CaIX-transfected HEK cells. Biodistribution experiments were performed in Balb/c nude mice, carrying subcutaneously BxPC3 tumors. RESULTS: In vitro studies demonstrated a higher binding to BxPC3, MCF7, and PDGFRβ-tr-HEK cells in comparison to negative control cell lines. Binding was inhibited up to 90% by the unlabeled PDGFR-P1 peptide. Organ distribution studies revealed a higher accumulation in BxPC3 tumors than in most organs. CONCLUSIONS: PDGFR-P1 is a promising candidate for targeting human PDGFRβ.